Explosive Power of Front Kick in The Perform of Martial Art Athletes - Bayu Prastowo; Safun Rahmanto (Universitas Udayana dan Diaspora Taipei Medical University, 2020)
Introduction: Martial art is a new sport that first competed in the 18th Asian Games. The front kick techniques in matches are more often used than other techniques. This study aims to identify whether Contract-Relax Stretching (CRS) affects the athlete's front kick explosive power performance. Methods: This study uses one group pre-test post-test design approach. The sample population was 30 respondents. Martial art athletes are given CRS. Results: Analysis probability value shows significant p<0.001, whereas vertical jump test increased the explosive power performance from poor to average and average to good. Conclusion: Performance of explosive power in the front kick of martial arts athletes increases after being given a CRS.